The Effect of Discipline and Work Ability Among Harvesters on Work Performance in Division II of the Adolina Plantation, PT. Perkebunan Nusantara IV Regional II - Rahmat Triandi; Hamzah Manurung (Lembaga Teewan Journal Solutions, 2026)
Plantation companies have a culture of enhancing work discipline and the work performance of each of their employees. In the development of an organisation within a company, this is naturally implemented and has become standard practice. At Adolina Plantation, Division II of PT Perkebunan Nusantara IV Regional II served as one of the sites for this research. The conclusions drawn from the research indicate that several assessments were carried out, namely work discipline, work attitude and work performance. The findings of this research indicate that, by examining the performance of the harvesters, their performance has a positive impact on the plantation’s productivity in the long term; work discipline influences the assessment process, thereby providing recognition to each harvester; and work ability yields increasingly better results, with the harvester’s work ability ultimately leading to improved work performance.